2015
DOI: 10.1128/genomea.01136-15
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Carbapenemase-Producing Klebsiella pneumoniae Myophage Matisse

Abstract: Klebsiella pneumoniae is a leading cause of nosocomial infections in the United States. Due to the emergence of multidrug-resistant strains, phages targeting K. pneumoniae may be a useful alternative against this pathogen. Here, we announce the complete genome of K. pneumoniae pseudo-T-even myophage Matisse and describe its features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
3
6
0
Order By: Relevance
“…The presence of the ndd gene ( orf276 ), the deduced amino acid sequence of which shared 100% identity with the nucleoid disruption protein of Klebsiella phage KP15, suggested a lytic lifestyle for vB_EaeM_φEap-3 ( Kesik-Szeloch et al, 2013 ). Comparative analysis of the whole genome sequence of vB_EaeM_φEap-3 against those of phages retrieved from the NCBI databases revealed that vB_EaeM_φEap-3 is most closely related to coliphages RB16 (NC_014467; Petrov et al, 2006 ) and RB43 (NC_007023; Petrov et al, 2006 ), Klebsiella phages KP15 (GU295964; Kesik-Szeloch et al, 2013 ), KP27 (HQ918180; Kesik-Szeloch et al, 2013 ), Matisse (KT001918; Provasek et al, 2015 ), and Miro (KT001919; Mijalis et al, 2015 ), Cronobacter phage vB_CsaM_GAP161 (JN882287; Abbasifar et al, 2012 ), and members of the myoviral subfamily Tevenvirinae, belonging to a genus of T4-like viruses ( Adriaenssens and Brister, 2017 ; Figure 6 ). A large percentage of the putative proteins that could be assigned a metabolic function were devoted to DNA metabolism and, replication ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the ndd gene ( orf276 ), the deduced amino acid sequence of which shared 100% identity with the nucleoid disruption protein of Klebsiella phage KP15, suggested a lytic lifestyle for vB_EaeM_φEap-3 ( Kesik-Szeloch et al, 2013 ). Comparative analysis of the whole genome sequence of vB_EaeM_φEap-3 against those of phages retrieved from the NCBI databases revealed that vB_EaeM_φEap-3 is most closely related to coliphages RB16 (NC_014467; Petrov et al, 2006 ) and RB43 (NC_007023; Petrov et al, 2006 ), Klebsiella phages KP15 (GU295964; Kesik-Szeloch et al, 2013 ), KP27 (HQ918180; Kesik-Szeloch et al, 2013 ), Matisse (KT001918; Provasek et al, 2015 ), and Miro (KT001919; Mijalis et al, 2015 ), Cronobacter phage vB_CsaM_GAP161 (JN882287; Abbasifar et al, 2012 ), and members of the myoviral subfamily Tevenvirinae, belonging to a genus of T4-like viruses ( Adriaenssens and Brister, 2017 ; Figure 6 ). A large percentage of the putative proteins that could be assigned a metabolic function were devoted to DNA metabolism and, replication ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, the interest of the scientific community is more and more focussed on alternative antibacterials such as bacterial predators—bacteriophages and phage-encoded endolysins. There is an increasing number of Klebsiella phages propagating on especially extended spectrum beta-lactamase (ESBL) and carbapenemase (KPC) producing isolates (Drulis-Kawa et al 2011; Kęsik-Szeloch et al 2013; Mijalis et al 2015; Provasek et al 2015; Wangkahad et al 2015; Jamal et al 2015), which enables analysis of homology and particular properties of this specific clade of phages. The proposed new Kp15virus genus within the subfamily Tevenvirinae groups five phages: Klebsiella phages vB_KpnM_KP15 and vB_KpnM_KP27 from the Polish collection; Klebsiella phages Matisse and Miro isolated in TX, USA; and Enterobacter phage phiEap-3 originating from Beijing, China.…”
Section: Discussionmentioning
confidence: 99%
“…The genome of phage P-KP2 is a linear double-stranded DNA that is comprised of 172,138 bp with a G + C content of 41.9%, and the termini of the phage genome is located at 38,590 bp (Supplementary Figure 2). Comparative analysis of the complete nucleotide sequence indicates that several phages show high similarity to P-KP2, including Enterobacter phage phiEap-3 (Zhao et al, 2019), Klebsiella phage Matisse (Provasek et al, 2015), Klebsiella phage KP27, Klebsiella phage KP15, Klebsiella phage PMBT1 (Koberg et al, 2017), Klebsiella phage KOX10, Klebsiella phage Miro (Mijalis et al, 2015), Escherichia phage phT4A (Pereira et al, 2017), and Klebsiella phage KOX8 (Table 1), which can be classified as a member of pseudo-Teven myophages which belong to "KP15likevirus" genus. Multiple genome alignment confirmed that these phages have parallel gene functional modules (Figure 3).…”
Section: Bioinformatics Analyses Of P-kp2 Genomementioning
confidence: 99%